2010
DOI: 10.1039/c0nr00390e
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring early stages of silver particle formation in a polymer solution by in situ and time resolved small angle X-ray scattering

Abstract: Silver particles have been prepared by reduction of silver nitrate with ascorbic acid in acidic aqueous solution containing a low concentration of a commercial polynaphthalene sulfonate polymer (Daxad 19) as dispersant agent. The reduction has been induced and controlled by the slow addition of ascorbic acid at a fixed rate; in this way, we were able to monitor the formation of a silver crystalline colloidal dispersion by in situ and time resolved Small Angle X-ray Scattering measurements. Modeling the scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…Scanning nano-probes with synchrotron radiation are now a hot topic in the investigation of structural fluctuations in biological systems [61][62][63][64]. In addition, fast detectors allow the in situ studies to monitor either physical or chemical modifications during data collection; for example, the few milliseconds readout time of the CMOS camera can be used for time-resolved measurements in different processes showing self-organization and pattern formation at the nanoscale [65][66][67][68][69]. Moreover, they allow us to prevent radiation damage on biological samples providing new key information [70][71][72].…”
Section: Introductionmentioning
confidence: 99%
“…Scanning nano-probes with synchrotron radiation are now a hot topic in the investigation of structural fluctuations in biological systems [61][62][63][64]. In addition, fast detectors allow the in situ studies to monitor either physical or chemical modifications during data collection; for example, the few milliseconds readout time of the CMOS camera can be used for time-resolved measurements in different processes showing self-organization and pattern formation at the nanoscale [65][66][67][68][69]. Moreover, they allow us to prevent radiation damage on biological samples providing new key information [70][71][72].…”
Section: Introductionmentioning
confidence: 99%
“…Bimetallic gold–copper alloy nanoparticles (Au 1– x Cu x NPs) have attracted much attention not only from a scientific perspective but also from an applied one, especially in the field of catalysis . Extensive efforts have been devoted to building synthesis strategies for Au 1– x Cu x NPs with well‐controlled chemical compositions, crystalline structures,, sizes, and shapes (morphologies) .…”
Section: Introductionmentioning
confidence: 99%
“…Among these techniques, in situ X‐ray absorption fine structure (XAFS) spectroscopy has received considerable attention, as it offers versatility. For example, changes in oxidation states, coordination, and bond formation can be monitored at the initial nucleation and growth stages of the NP formation, and information can be obtained about the local environment with chemical sensibility, even in the absence of a crystalline phase , . Although several in situ studies have been performed to monitor the formation of bimetallic NPs, most of them have dealt with aqueous‐phase reactions, and only a few limited reports have dealt with the formation of bimetallic NPs in the organic phase …”
Section: Introductionmentioning
confidence: 99%
“…Previous TEM investigations on the same samples showed the presence of twinning defects common in metallic particles [21,22] and in situ time-resolved small angle X-ray scattering measurements also revealed that the tabular particles result from the aggregation of primary particles with size of about 30 nm [23]. The electron diffraction SAED pattern could be indexed as a silver face-centered cubic structure (JCPDS-04-0783) [21].…”
Section: Resultsmentioning
confidence: 73%
“…In our previous studies [21,25], we determined the crystallite size using Scherrer's equation corrected with an external standard for instrumental error, and showed that in all cases crystalline sizes varied between 20 nm and 33 nm. In the case of single crystal hexagonal particles, the crystal size of 33 nm, found by applying Scherrer's equation, was sensibly less than the particle size (diagonal was ca.…”
Section: Resultsmentioning
confidence: 99%